Sosialisasi Pembuatan Pelepah Kelapa Sawit Menjadi Biobriket Di Desa Sungai Putih, Kecamatan Kampa, Kabupaten Kampar - Rozan Alfattah; Ledy Diana; Adinda Natasya Putri; Joy Alberto Neonane; Kevin Arsenta; Muhammad Khori; Zakky Zakwan Arfa; Elisa Dwi Aulia; Putri Novela Smatupang; Laura Laurensia; Arum Dwi Alwita; Nelvi Zulhijriani Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The increase in fossil energy consumption accelerates the depletion of non-renewable energy reserves, highlighting the urgent need for innovative alternative energy sources such a biomass. Oil palm fronds biomass represents an underutilized potential in Sungai Putih Village, Kampa District, Kampar Regency. Therefore, a socialization activity on making bio-brickets from oil palm fronds is needed as an effort to process waste, empower the community to improve the village economy. The socialization activity was held on Sunday, July 13, 2025, in front of the multipurpose room of Sungai Putih Village. The methods used in the activity included observing the village's potential, identifying problems, and implementations socialization activities accompanied by hands-on practice in making bio-brickets. The results of the socialization showed that oil palm fronds have the potential to be processed into bio-brickets. The bio-bricket production process includes drying the raw materials, burning, sieving, molding, and drying again. Bio-brickets have economic value and can serve as an alternative source of fuel. The main challenge faced is the community’s limited understanding of the marketing stages. This socialization activity was restricted to bio-brickets production, revealing the necessity for additional guidance to foster continued growth.